Thwarted Belongingness and Perceived Burdensomeness: Construct Validity and Psychometric Properties of the Interpersonal Needs Questionnaire - Van Orden, Kimberly A. (2011)
The present study examines the psychometric properties and construct validity of scores derived from the Interpersonal Needs Questionnaire (INQ) using latent variable modeling with five independent samples varying in age and level of psychopathology. The INQ was derived from the Interpersonal Theory of Suicide and was developed to measure thwarted belongingness and perceived burdensomeness—both proximal causes of desire for suicide. Results support that thwarted belongingness and perceived burdensomeness are distinct, but related constructs and that they can be reliably measured. Further, multiple group analyses were consistent with invariance for younger vs. older adults and non-clinical versus clinical populations thereby supporting the relevance of these constructs to diverse populations. Finally, both constructs demonstrated convergent associations with related interpersonal constructs—including loneliness and social support for belongingness and social worth and death ideation for burdensomeness—as well as prospective associations with suicidal ideation.